SIGNIFIKANSI MUNASABAH AYAT AL-QURAN DALAM TAFSIR PENDIDIKAN - Suryadi, Rudi Ahmad (ULUL ALBAB Jurnal Studi Islam, 2016)
One of the popular study in Islamic education is Tafsir Tarbawi. It offers a thematic idea on education based on interpretation approach. The knowledge of Munasabah al Ayat is important to note. It showed the unity and comprehensive meaning. Understanding Munasabah al Ayat is a step that must be taken to assess the understanding of education in the perspective of the Quran, particularly on the application of tafsir al maudhu’i. It will help researchers to understand the purpose and meaning of verses inferred based on the mindset that made the paradigm of the review.